Synergistic antiproliferative and pro-apoptotic effects of Prunus armeniaca and bee venom on breast cancer cells - Kadasah, Sultan F.; Alrefaei, Abdulmajeed F.; Abd Al Galil, Fahd Mohammed; Alqahtani, Abdulaziz M.S. (Frontiers in Oncology, 2025)
IntroductionBreast cancer is the most prevalent malignancy among women worldwide, with triple-negative breast cancer (TNBC) posing significant therapeutic challenges due to its aggressive nature and lack of targeted treatments. Natural compounds such as Prunus armeniaca (PA) and bee venom (BV) have demonstrated anticancer potential.MethodsThis study evaluates the synergistic effects of PA and BV on breast cancer cells, focusing on proliferation, apoptosis, and invasion. MCF-7 and MDA-MB-231 breast cancer cells were treated with varying concentrations (0–500 µg/mL) of PA, BV, and their combination. Cytotoxicity was assessed via the MTT assay, and the IC50 values were determined using GraphPad Prism. Colony formation, phase contrast microscopy, Acridine Orange/Ethidium Bromide (AO/EB) staining, transwell invasion, and Western blot assays were performed to evaluate proliferation, apoptosis, and invasion. Statistical significance was determined using one-way ANOVA.Result and discussionThe combination of PA and BV significantly enhanced cytotoxicity, with IC50 values reduced to 35.148 µg/mL in MCF-7 cells and 73.80 µg/mL in MDA-MB-231 cells, suggesting a synergistic effect. Colony formation assays revealed an 83% reduction at the highest dose (70.3 µg/mL). Morphological assessment showed characteristic apoptotic features, including cell shrinkage and membrane blebbing. AO/EB staining confirmed apoptosis induction, with apoptotic cells increasing from 3.2% in controls to 65.3% at 70.3 µg/mL. Western blot analysis demonstrated Bax upregulation and Bcl-2 downregulation, supporting apoptosis activation. Transwell invasion assays indicated a 59% reduction in cell invasion, suggesting that BV-PA effectively suppresses metastasis. BV-PA exhibits potent antiproliferative, pro- apoptotic, and anti-invasive effects in MCF-7 cells. These findings highlight its potential as a natural therapeutic strategy for breast cancer treatment, particularly TNBC. Further investigations are warranted to explore its molecular mechanisms and in vivo.